2015
DOI: 10.1007/s10529-015-1870-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbial volatile organic compounds produced by wood-decay fungi

Abstract: As both fungi produced specific MVOCs in the course of wood degradation indicates the possibility of the application of MVOCs as detection markers for wood-decay fungus existing in woody materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Methyl furoates have been identified as MVOCs in fungal cultivations on Japanese beech wood (Konuma et al . 2015), but no clear relation with any of the compounds with either brown rot of white rot decay type could be recognized. In our study, NMDS orientation analysis moreover visualized the correspondence of methyl 3-furoate with white rot decay type, especially pointing the relation with fungal-produced manganese peroxidase activity, which is indicative of a strong oxidoreductive attack on lignin in wood (Hatakka and Hammel 2010; Floudas et al .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Methyl furoates have been identified as MVOCs in fungal cultivations on Japanese beech wood (Konuma et al . 2015), but no clear relation with any of the compounds with either brown rot of white rot decay type could be recognized. In our study, NMDS orientation analysis moreover visualized the correspondence of methyl 3-furoate with white rot decay type, especially pointing the relation with fungal-produced manganese peroxidase activity, which is indicative of a strong oxidoreductive attack on lignin in wood (Hatakka and Hammel 2010; Floudas et al .…”
Section: Discussionmentioning
confidence: 93%
“…Together with an array of terpenoids, methyl furoates (predicted as linoleic acid oxidation derived products) were identified in another study as MVOC products in beech-wood single-species cultures of a brown rot fungus ( Fomitopsis palustris ) and a white rot fungus ( Trametes versicolor ) (Konuma et al . 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that fungal emission patterns can be species-specific, and chemotyping is possible for some species and functional groups (Müller et al 2013;Redeker et al 2018). Species-specific VOCs have already been defined for a few polypore species (Marshall 1970;Cowan 1973;McAfee & Taylor 1999;Rapior et al 2000;Rosecke et al 2000;Ziegenbein et al 2010;Konuma et al 2015). More generally, this confirms that direct mass spectrometry allows for a reliable species identification of wood decaying polypores, including a discrimination between F. fomentarius and Fomes inzengae (Pristas et al 2017).…”
Section: Volatile Organic Compoundsmentioning
confidence: 54%
“…At first, it is surprising that pure cultures produce a higher diversity and higher concentrations of VOCs than basidiomes. Wood-decaying fungi produce specific VOCs during wood degradation, and emission patterns depend on both the cultivation stage and the substrate (wood chips or potato dextrose agar), suggesting that wood degradation might activate synthetic pathways such as VOC production (Konuma et al 2015). Emission patterns of basidiomes could differ because hyphae are not physiologically active any more: no wood degradation occurs in basidiomes, and in those the hyphae have mainly structural (skeletal hyphae) and reproductive functions.…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…During this process, different types of fungi produce a unique grouping of microbial volatile organic compounds (MVOCs), which can also be used for species identification. This phenomenon indicates the possibility of using MVOCs as detection markers for wood decay fungus [1].…”
Section: Introductionmentioning
confidence: 99%